Uber-nization of transport: An investigation into the sustainability of ride-sharing applications in Malaysia - Ong, Derek Lai Teik *; Tee, Sherlyn Yan Ven; Lim, Martin Yek Houng (2017)
Commuting trips is projected to hit 72 million alongside the urban population growth 75% by 2020. However, transportation mode availability has only grown by 8% over the last 5 years, thereby creating an unfulfilled demand gap in transportation. This has led to delays in public transportation, causing a ripple effect on work productivity. Suppressed demand affects riders’ decision to use public transportation, spurred the use ride-sharing in the past 2 years in Malaysia. The research aims to investigate the factors that influence the adoption of ride-sharing services and to identify target segments of ride-sharing users in order to tailor offerings and solutions to them, thus assisting the government and industry to improve the sustainability of the transportation landscape of the country. The integration of the Technology Acceptance Model and Theory of Planned Behaviour adopted for this research aims to understand the adoption usage of the ride sharing app user’s consumer behavior. From a purposive convenient snowball sampling of 107 out 144 samples multiple linear regression and Hayes Process for mediation show significant results between the constructs of Perceived Ease of Use, Perceived Usefulness, Attitude and Intention in using ride sharing apps. The analysis was followed by a two-step cluster deriving 4 distinct clusters of ride-sharing users with individual consumer behavior and corresponding demographic characteristics. Results of this research can see larger applications replicated across various contextual scenarios and geographies not limited to just the transportation industry.